Emotional education for sustainable development: a curriculum analysis of teacher training in Portugal and Spain - Cristóvão, Ana Maria; Valente, Sabina; Rebelo, Hugo; Ruivo, Ana Francisca (Frontiers in Education, 2023)
The challenges before us indicate that the current model of societal development is creating problems for our planet, such as the climate crisis, the increase in inequalities, and the emergence of new phenomena of exclusion and social malaise. The 2030 Agenda for Sustainable Development presents 17 Sustainable Development Goals (SDGs) that define priorities for a more sustainable world. Education is one of the main ways to create a peaceful and sustainable world for the survival and prosperity of present and future generations. The literature highlights the importance of teachers’ socio-emotional skills and the promotion of socio-emotional skills in their students. The Emotional Education approach proposes a new pedagogical paradigm, in which the individual is encouraged to develop intra-and interpersonal skills, enabling them to deal creatively with their conflicts and those encountered in the environment, and increasing their self-confidence and emotional balance. These skills will contribute to the achievement of the objectives of the SDG. Based on these arguments, the study and systematization of social–emotional education is urgent. In this study, a documentary analysis was carried out of the programs of study offered as part of the degrees (undergraduate and master’s level) provided for the training of preschool and primary teachers in Portugal and Spain, with the aim of understanding whether these courses offer content relating to Emotional Education. Programs of study from 127 public and private higher education institutions across both countries were analyzed. The analysis revealed that in Portugal, despite an increase in interest in issues relating to emotional intelligence in schools, this interest is not yet reflected in the initial training of preschool and primary teachers (with only two universities, both private institutions, offering Emotional Education content). In Spain, there is already a considerable number of institutions (29) that offer Emotional Education, but this corresponds to only 30% of the universities listed. The results of this study indicate that there is still some distance to go to make Emotional Education an effective component of the curricula of future teachers and thus contribute to achievement of the SDGs.